Questing through Acid–Base Chemistry: An RPG-Based Educational Game for High School Learning - Syarifatul Mubarak; Muhammad Thobrhoni Noor Khatmunnubuwah; Raehanah Raehanah (Online Learning In Educational Research (OLER), 2025)
The background of this study was triggered by the long time period in which students spend playing games and the ineffective use of learning media in teaching chemistry subjects. The purpose of the study is to design a model for learning through an Educational Role Playing Game (RPG) to be feasible and practical in teaching acid-base principles for grade XI students. In addition, the study Using the analysis, design, development, implementation, and evaluation (ADDIE) approach in conjunction with a research and development approach. The participants in this study were media experts, subject matter experts in the area of chemistry, chemistry teachers, and learners in Grade XI from MAN 1 Mataram. The study used interviews and questionnaires as techniques to collect data from the study participants. With validation scores of 92.85% from media professionals, 90.62% from subject experts, and 97.36% from chemistry professors, the study's findings demonstrate the viability of the suggested learning game. Students with an 85.90% practicality level also provided a very positive feedback. This outcome also leads to the conclusion that this RPG-based instructional game is workable and useful for improving students' comprehension of acids and bases